2006
DOI: 10.1002/asi.20336
|View full text |Cite
|
Sign up to set email alerts
|

The Open Video Digital Library: A Möbius strip of research and practice

Abstract: The Open Video Digital Library (OVDL) provides digital video files to the education and research community and is distinguished by an innovative user interface that offers multiple kinds of visual surrogates to people searching for video content. The OVDL is used by several thousand people around the world each month and part of this success is due to its user interface. This article examines the interplay between research and practice in the development of this particular digital library with an eye toward le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
21
0
6
Order By: Relevance
“…These results were incorporated into an operational system (Open Video Project; http://open-video.org). The results of these studies are reported in more than a dozen papers in the HCI and IR literature (see Marchionini, Wildemuth, & Geisler, 2006, for a summary). Assessments were made for different variations of single keyframes (poster frames), storyboards (arrays of keyframes), slide shows, and fast forwards for a series of recognition and gist determination tasks, using task accuracy, time, and a battery of affective measures.…”
Section: Example: Results In Contextmentioning
confidence: 99%
“…These results were incorporated into an operational system (Open Video Project; http://open-video.org). The results of these studies are reported in more than a dozen papers in the HCI and IR literature (see Marchionini, Wildemuth, & Geisler, 2006, for a summary). Assessments were made for different variations of single keyframes (poster frames), storyboards (arrays of keyframes), slide shows, and fast forwards for a series of recognition and gist determination tasks, using task accuracy, time, and a battery of affective measures.…”
Section: Example: Results In Contextmentioning
confidence: 99%
“…This though would require significant effort and is unlikely to happen in the near future. Other possibilities include the reporting of additional evaluation metrics [12], the move away from analyst-oriented deep information seeking tasks, or the change to more generalized corpora which are less dependent on "shots".…”
Section: Discussionmentioning
confidence: 99%
“…However, the Open Video Digital Library (OVDL) has provided a repository of digital content, and an open interface for browsing and searching the data [12]. Despite the lack of shared interaction data from TRECVID evaluations, the common collections and benchmarking resources provided by this initiative have facilitated a great deal of research into both interactive retrieval and its associated human factors.…”
Section: Related Workmentioning
confidence: 99%
“…The algorithms were tested with the sequence SunEarth Connection, a video downloaded from the Open Video repository [25] in MPEG-2 format, and transcoded to H.264/AVC using the JM 12.4 reference implementation. The sequence has 11,593 frames of 720 Â 480 pixels at 30 frames per second.…”
Section: Methodsmentioning
confidence: 99%